Dressing the part: The influence of police attire on outcomes in a simulated traffic violation case - Crough, Quintan (International journal of police science & management, 2023)
Consistently outlined in juror decision-making research is that seemingly irrelevant variables (e.g., the appearance of defendants or plaintiffs) can impact judicial proceedings. Although police officers frequently appear in courtrooms, limited literature exists that assesses the impact of officer attire in this setting. The current study exposed participants to a mock-trial transcript outlining a traffic violation case in which officer gender and attire were manipulated. Participants then rendered a verdict, before providing ratings of officer credibility and police legitimacy, using the Police Legitimacy Scale (PLS). The female officer was viewed as significantly more credible than the male officer and participants’ PLS scores predicted their verdicts. Although no attire differences were found, findings might have implications for uniform policies.